IMMUNOHISTOCHEMICAL AND MORPHOMETRIC STUDY OF ADENOHYPOPHYSEAL GONADOTROPIC CELLS IN MALE CADAVERS OF DIFFERENT AGES - Čukuranović Kokoris, Jovana; Jovanović, Ivan; Ugrenović, Slađana; Stojanović, Vesna; Pavlović, Miljana; Kundalić, Braca; Živković, Vladimir; Antić, Milorad; Čukuranović, Rade (Acta medicae Medianae, 2021)
The literature data suggest that in gonadotropic cells there occurs a functional decline with advancing age, while the data concerning structural changes in these cells are rather scarce. The aim of this paper was to detect and quantify the changes in human gonadotropic cells of the anterior pituitary in male cadavers of different ages using immunohistochemical and morphometric methods. The material in this study consisted of adenohypophyseal tissue from 14 male cadavers of different ages, starting from the fourth decade of life. Adenohypophyseal tissue sections were routinely histologically processed and stained with immunohistochemical monoclonal anti-LH antibody to detect gonadotropic LH cells. Digital images of the visual fields of immunohistochemically processed adenohypophyseal sections were then morphometrically analyzed using the Image J system. Statistical analysis was performed using the SPSS statistical software package. The results of the morphometrical analysis showed that volume density of LH cells did not change significantly with advancing age, while their area, perimeter and Feret’s diameter increased statistically significantly. Nuclear morphometric parameters did not change significantly, while the nuclear-cytoplasmic ratio of LH cells decreased with ageing, with a statistically significant decline observed in cases aged over 70 years. Based on the obtained results the conclusion may be drawn that the density of LH cells does not change significantly with ageing, but that they undergo hypertrophy in order to maintain normal hormonal secretion. Long-lasting hypertrophy of these cells ultimately lead to their functional decline, which reaches statistical significance after 70 years of age.